What attracts human capital?: understanding the skill composition of interregional job matches in Germany - Arntz, Melanie (Discussion paper, 2006)
By examining the destination choice patterns of heterogenous labor, this paper tries to explain the skill composition of internal job matching flows in Germany. Estimates from a nested logit model of destination choice suggest that spatial job matching patterns by high-skilled individuals are mainly driven by interregional income differentials, while interregional job matches by less-skilled individuals are much more affected by regional differentials in job opportunities. Regional differentials in non-pecuniary assets slightly contribute to spatial sorting processes in Germany. Such differences in destination choices by skill level are partly modified by different spatial patterns of job-to-job matches and job matches after unemployment. Simulating job matching patterns in a scenario of economic convergence between eastern and western Germany demonstrates that wage convergence is the most effective means of attracting human capital to eastern Germany.
Literaturverz. S. 33-36
Internetausg.: ftp://ftp.zew.de/pub/zew-docs/dp/dp06062.pdf
Keywords: Deutschland